Cluster of Severe Acute Respiratory Syndrome Coronavirus 2 Infections Linked to Music Clubs in Osaka, Japan. (25th August 2020) - Sugano, Nobuhiko; Ando, Wataru; Fukushima, Wakaba
Abstract: Background: It is important to understand the mode of transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) for disease control. We aimed to clarify how soon SARS-CoV-2 transmission can occur after infection by asymptomatically infected individuals. Methods: We analyzed the publicly available epidemiological information for a cluster of 108 cases of coronavirus disease 2019 (COVID-19) cases in Osaka, Japan. Results: Among cases, 51 cases attended a live music club only once and were considered to have a single visit. Ten remained asymptomatic at the time of COVID-19 diagnosis by reverse-transcription polymerase chain reaction, which was on average 20 days after exposure. Three routes of secondary transmission were identified, with 2–4 days from infection to transmission. All index cases for secondary transmission were asymptomatic at the time of contact with other people. Based on the date of symptom onset in the remaining 41 cases, the period from exposure to illness ranged from 2 to 17 days. Conclusions: Seemingly healthy people could spread SARS-CoV-2 during intense activities in enclosed environments without sufficient ventilation. Asymptomatically infected persons can transmit the virus as soon as 2 days after infection. Continuous efforts to avoid crowding and to maintain personal hygiene are needed for effective control of COVID-19. Abstract : Investigation of a cluster of 108 severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections linked to music clubs revealed that asymptomatically infected persons can transmit SARS-CoV-2 as soon as 2 days after infection. Asymptomatic transmission appeared to be efficient in crowded indoor settings.